The effects of co-workers’ social undermining behaviour on employees’ work behaviours - Ong, L.D.; Tay, A. (2015)
This study examines the extent to which trust in co-workers mediates the relationships between co-workers’ social undermining behaviour and employees’ work behaviours. Two structured questionnaires were designed to collect data from employees and their co-workers. The mediating role was investigated using Structural Equation Modelling (SEM) from 502 employees in Malaysia. The SEM analysis showed that co-workers’ social undermining behaviour had indirect relationships with employees’ work behaviours via the mediating role of trust in co-workers. The results of this study highlighted the importance of curbing social undermining behaviour in the workplace in order to instil trust among employees and better work behaviours in the workplace.